Role of the mucin-like glycoprotein FCGBP in mucosal immunity and cancer - Liu, Qiao; Niu, Xia; Li, Yang; Zhang, Jia-rui; Zhu, Shao-jun; Yang, Qi-yuan; Zhang, Wei; Gong, Li (Frontiers in Immunology, 2022)
IgGFc binding protein (FCGBP) is a mucin first detected in the intestinal epithelium. It plays an important role in innate mucosal epithelial defense, tumor metastasis, and tumor immunity. FCGBP forms disulfide-linked heterodimers with mucin-2 (MUC2) and members of the Trefoil Factor Family (TFF). These formed complexes inhibit bacterial attachment to mucosal surfaces, affect the motility of pathogens and support their clearance. Altered FCGBP expression levels may be important in pathologic processes of Crohn’s disease and ulcerative colitis. FCGBP is also involved in regulating the infiltration of immune cells into tumor microenvironments. Thus, the molecule is a valuable marker of tumor prognosis. This review summarizes the functional relevance and role of FCGBP in immune responses, disease development and highlights the potential role in diagnosis and predicting tumor prognosis.